2007
DOI: 10.4049/jimmunol.179.11.7254
|View full text |Cite
|
Sign up to set email alerts
|

Specific Immunogenicity of Heat Shock Protein gp96 Derives from Chaperoned Antigenic Peptides and Not from Contaminating Proteins

Abstract: The peptide-binding property of MHC is central to adaptive immunological functions. A similar property of heat shock proteins (HSPs) hsp70 and hsp90 has been implicated in Ag presentation by MHC and in cross-priming. The peptide-binding pocket of hsp70 has been characterized structurally and functionally and a peptide-binding site in gp96 (of hsp90 family) has been defined. Nonetheless, questions persist whether the specific immunogenicity of HSP preparations derives from the peptides chaperoned by the HSPs or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 33 publications
(42 reference statements)
1
30
1
Order By: Relevance
“…Consequently, gp96-peptide complexes extracted from cancer cells harbor tumor-specific peptides and are immunogenic, offering a tool for active immunization against the tumor (13)(14)(15)(16)(17). Therefore, immunologists speculate that every preparation of gp96-associated peptide pool is different.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, gp96-peptide complexes extracted from cancer cells harbor tumor-specific peptides and are immunogenic, offering a tool for active immunization against the tumor (13)(14)(15)(16)(17). Therefore, immunologists speculate that every preparation of gp96-associated peptide pool is different.…”
Section: Resultsmentioning
confidence: 99%
“…Also, gp96 regulates the activity of plasmacytoid dendritic cells via CD91 (38,39). The gp96 also enables specific immune responses by potentiating cross presentation of immunogenic peptides on MHC class I; thus, facilitating antigen specific activation of cytotoxic T cells (40)(41)(42)(43). A phase II trial is ongoing, in which patients are immunized with complexes of gp96 in combination with tumor antigens to promote presentation of these tumor-derived antigens by APC (44).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they demonstrated that the specific immunogenicity of Gp96 preparations was due to MHC Class-I epitope precursors associated with Gp96 and not to contaminating b-galactosidase protein. 127 Furthermore, an extensive report convincingly underscores the intrinsic cell-signaling properties of the molecular chaperones. 128 However, some doubts remain whether the therapeutic immunological effects of Gp96 treatment, such as cytokine stimulation and CTL responses, are due to contamination with lipopolysaccharide or result from the HSPs themselves and/or the chaperoned peptides.…”
Section: Discovery Of Hsps Gp96 and Their Immunological Propertiesmentioning
confidence: 97%